The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1128/jb.178.24.7276-7284.1996
|View full text |Cite
|
Sign up to set email alerts
|

Induction of actinorhodin production by rpsL (encoding ribosomal protein S12) mutations that confer streptomycin resistance in Streptomyces lividans and Streptomyces coelicolor A3(2)

Abstract: A strain of Streptomyces lividans, TK24, was found to produce a pigmented antibiotic, actinorhodin, although S. lividans normally does not produce this antibiotic. Genetic analyses revealed that a streptomycin-resistant mutation str-6 in strain TK24 is responsible for induction of antibiotic synthesis. DNA sequencing showed that str-6 is a point mutation in the rpsL gene encoding ribosomal protein S12, changing Lys-88 to Glu. Gene replacement experiments with the Lys883Glu str allele demonstrated unambiguously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
199
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(205 citation statements)
references
References 49 publications
6
199
0
Order By: Relevance
“…MYM‐TAP liquid medium (with 400 μL of trace element solution44 added per 200 mL of medium added after autoclaving) was used to grow Streptomyces strains for venemycin production and for RNA isolation from S. coelicolor M1825. For the halogenation studies we used Minimal Medium (MM)44 supplemented with NaCl or NaBr (0.5 g L −1 ), and modified versions of R3 medium45 consisting of glucose (10 g L −1 ), yeast extract (5 g L −1 ), casamino acids (100 mg L −1 ), proline (3 g L −1 ), MgSO 4 ⋅ 7 H 2 O (10 g L −1 ), CaSO 4 ⋅ 2 H 2 O (4 g L −1 ), K 2 SO 4 (200 mg L −1 ), KH 2 PO 4 (50 mg L −1 ), TES [ N ‐tris(hydroxymethyl)methyl‐2‐aminoethanesulfonic acid, 5.6 g L −1 ], trace elements (as described for R2YE medium44) and NaCl or NaBr or both (1 g L −1 ); the media were adjusted to pH 7.2 with NaOH and autoclaved. Streptomyces liquid cultures were performed in medium (50 mL) in 250 mL flasks containing stainless steel springs to promote dispersed growth with at least two replicates.…”
Section: Methodsmentioning
confidence: 99%
“…MYM‐TAP liquid medium (with 400 μL of trace element solution44 added per 200 mL of medium added after autoclaving) was used to grow Streptomyces strains for venemycin production and for RNA isolation from S. coelicolor M1825. For the halogenation studies we used Minimal Medium (MM)44 supplemented with NaCl or NaBr (0.5 g L −1 ), and modified versions of R3 medium45 consisting of glucose (10 g L −1 ), yeast extract (5 g L −1 ), casamino acids (100 mg L −1 ), proline (3 g L −1 ), MgSO 4 ⋅ 7 H 2 O (10 g L −1 ), CaSO 4 ⋅ 2 H 2 O (4 g L −1 ), K 2 SO 4 (200 mg L −1 ), KH 2 PO 4 (50 mg L −1 ), TES [ N ‐tris(hydroxymethyl)methyl‐2‐aminoethanesulfonic acid, 5.6 g L −1 ], trace elements (as described for R2YE medium44) and NaCl or NaBr or both (1 g L −1 ); the media were adjusted to pH 7.2 with NaOH and autoclaved. Streptomyces liquid cultures were performed in medium (50 mL) in 250 mL flasks containing stainless steel springs to promote dispersed growth with at least two replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Here we focus on the original studies that provided the impetus for the field as well as a molecular rationale for ribosome engineering. As alluded to above, wt S. lividans TK21 normally does not produce Act, even though it contains a complete act biosynthetic gene cluster (Shima et al 1996). The original study by Ochi and colleagues investigated how the streptomycinresistant S. lividans strain TK24 produced abundant quantities of Act (Fig.…”
Section: Motivationmentioning
confidence: 99%
“…The inventors of the method were inspired by the observation that a mutated, streptomycin-resistant strain of Streptomyces lividans produced the blue pigment actinorhodin (Act, Fig. 1, 2), whereas the parent strain, from which the mutant was derived, did not (Shima et al 1996). They mapped the mutation to a ribosomal protein and showed that only the mutant ribosome led to activation of the silent Act gene cluster (act), thus demonstrating translational control in Act biosynthesis.…”
Section: Motivationmentioning
confidence: 99%
“…Working with the genera Streptomyces and Bacillus, the correlation between the stringent response and antibiotic production has been established. In the absence of a functional relA or rplK gene, antibiotic production by these organisms is remarkably reduced or lost (11)(12)(13)(14). Therefore, the initiation of antibiotic production is considered to be positively regulated by the stringent response (15-18), * This work was supported by a grant from the Organized Research Combination System of the Science and Technology Agency of Japan.…”
mentioning
confidence: 99%